2019
DOI: 10.1002/htj.21537
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in a triangular cavity filled with air under the effect of external air stream cooling

Abstract: Natural convection in a triangular cavity filled with air is investigated numerically. In this paper, the cavity is exposed to air stream cooling exerted on its sides and it is heated by a fixed heat flux from the base. The air inside the cavity is assumed to be laminar and obeying Boussinesq approximation. The governing equations are solved numerically using the finite volume technique with SIMPLE algorithm. The results are achieved with a range of Rayleigh number (104 < Ra < 107), free stream Reynolds number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This indicated that HT is influenced by the deformation of the lower wall of the cavity. Saleem and Alshara 22 focused on a numerical examination of NC flow in a triangular cavity exposed to a cold air stream from both side walls. They found that the AR influences HT, with an 83% increase as AR goes from 0.25 to 1.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that HT is influenced by the deformation of the lower wall of the cavity. Saleem and Alshara 22 focused on a numerical examination of NC flow in a triangular cavity exposed to a cold air stream from both side walls. They found that the AR influences HT, with an 83% increase as AR goes from 0.25 to 1.…”
Section: Introductionmentioning
confidence: 99%
“…For different inclination angles, the LBM with a single relaxation time (SRT) is employed as a computational fluid dynamics (CFD) alternative method to explore the flows of water and air in a triangular enclosure 35,36 . Saleem et al 37 investigated the influence of the aspect ratio, in addition to the inclination effect, on air convective flow in a triangular enclosure. The cavity is heated by fixed heat flux from the base and is subjected to air‐stream cooling on its sides.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous of the previous researches on natural convection have focused on rectangular enclosures with a vertical (Rayleigh-Benard convection) or a horizontal gradient of temperature [9,10], while others have studied rectangular cavities partially heated or cooled [11,12]. Natural convection in triangular enclosures [13][14][15] has been treated also due to its widespread use in many industrial and domestic systems such as building roofs and solar power, etc. Yesiloz et al [16] and Oztop et al [17] have studied experimentally the natural convection of water and air, respectively, in a right-angled triangular cavity.…”
Section: Introductionmentioning
confidence: 99%